2021
DOI: 10.1007/s11356-021-12553-1
|View full text |Cite
|
Sign up to set email alerts
|

Coronaviruses in humans and animals: the role of bats in viral evolution

Abstract: Bats act as a natural reservoir for many viruses, including coronaviruses, and have played a crucial epidemiological role in the emergence of many viral diseases. Coronaviruses have been known for 60 years. They are usually responsible for the induction of mild respiratory signs in humans. However, since 2002, the bat-borne virus started to induce fatal epidemics according to WHO reports. In this year, the first serious human coronavirus epidemic (severe acute respiratory syndrome; SARS) occurred (China, 8098 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 120 publications
(149 reference statements)
0
44
0
Order By: Relevance
“…Coronaviruses are zoonotic viruses; SARS-CoV was transmitted from civet cats to humans and MERS-CoV from dromedary camels to humans. 1 The worldwide pandemic of Coronavirus Disease 2019 (COVID- 19), is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), first discovered in Wuhan, China in 2019. [2][3][4] Common manifestations of COVID-19 infection include respiratory symptoms, cough, fever, breathing difficulties and anosmia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coronaviruses are zoonotic viruses; SARS-CoV was transmitted from civet cats to humans and MERS-CoV from dromedary camels to humans. 1 The worldwide pandemic of Coronavirus Disease 2019 (COVID- 19), is caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), first discovered in Wuhan, China in 2019. [2][3][4] Common manifestations of COVID-19 infection include respiratory symptoms, cough, fever, breathing difficulties and anosmia.…”
Section: Introductionmentioning
confidence: 99%
“…WHO recommendations to prevent infection spread include frequent hand washing, covering nose and mouth when sneezing and coughing, and avoiding close contact with anyone showing symptoms of respiratory symptoms such as coughing and sneezing. 1 There is currently no specific drug therapy or vaccine available to treat COVID- 19. Antimalarial drugs such as hydroxychloroquine and azithromycin, as well as antifilarial drugs such as ivermectin and antiviral drugs such as favipiravir, remdesivir, and umifenovir, have been studied.…”
Section: Introductionmentioning
confidence: 99%
“…As of June 30, 2021, over 180 million cases of COVID-19 have been reported, and more than 3.9 million lives claimed worldwide ( https://covid19.who.int/ ). Due to its fast spread and high mortality rate, scientists have worked on all fronts to characterize the virus ( El-Sayed and Kamel, 2021 ; Harrison et al, 2020 ; Yao et al, 2020 ) and reported clinical symptoms associated with the viral disease ( El-Sayed et al, 2021a , El-Sayed et al, 2021b ).…”
Section: Introductionmentioning
confidence: 99%
“…BCoV causes respiratory and enteric infections in cattle (Clark 1993 ) while HCoV isolate OC43 the causative agent of common cold in humans. In 1937, avian infectious bronchitis (IB) was the first characterized coronavirus (El-Sayed and Kamel 2021 ). Human coronaviruses (HCoV) were identified in the 1960s and later, the bovine coronavirus (BCoV) in the 1970s (El-Sayed and Kamel 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 1937, avian infectious bronchitis (IB) was the first characterized coronavirus (El-Sayed and Kamel 2021 ). Human coronaviruses (HCoV) were identified in the 1960s and later, the bovine coronavirus (BCoV) in the 1970s (El-Sayed and Kamel 2021 ). To date, seven different CoVs have been identified in humans.…”
Section: Introductionmentioning
confidence: 99%